Implementasi Ganti Rugi (Ta'wid) dalam Akad Muamalah dan Korelasinya dengan Tanggungjawab dalam Hukum Perdata (al-Mas'uÌ‚liyah al-Madaniyah Mesir dan Syuria) - M, Muhajirin (Universitas Muhammadiyah Prof DR HAMKA, 2018)
The obligation to provide compensation in civil law (Muamalah) and criminal (Jinayah) based on the formula in the Qur'an, al-Hadith and Ijma 'Ulama. The implementation of Ta'widh (compensation) can be included in the discussion of civil law (muamalah) and criminal law (jinayah). The purpose of this study is to find out the concept of compensation in the perspective of Islamic law and its implementation in muamalah contract. The theoretical framework used is Maqashid al-Syarí®'ah. While the research method used is the Normative Juridical method, namely the method of legal research carried out by examining library research. The research approach used is the Comparative Approach. This study concludes that the implementation of compensation is very broad because it can enter the realm of muamalah (civil) and jinayah (criminal), in contrast to the decision of the fatwa of the Indonesian Ulama Council (MUI) Number 43 of 2004 concerning Compensation (dhamí¢n / ta'wí®dh), where compensation can only be applied to transactions (contracts) that cause debt (dain), such as Salaam, Istishní¢ ', Murí¢bahah and Ijí¢rah. Keywords: Ta'widh, Muamalah, dan Maqí¢shid al-Syarí®Ê»ah.